Physico-chemical characteristics of edible film from breadfruit starch (Artocarpus altilis) and beeswax - Ermawati, Tesya Anggun; Rahmadhia, Safinta Nurindra (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Starch or other polysaccharides-based packaging is environmentally friendly and can be used as an alternative to tackle the environmental issue. Bio-based polymers can be made into flexible packaging sheets used as edible films. Breadfruit (Artocarpus altilis) is one of the most common sources of starch, and it could be used to make edible films. When beeswax was added, the amount of water vapor permeability (WVP) decreased, and the mechanical properties of starch-based edible films improved. This study aimed to identify the effects of breadfruit starch and beeswax, as well as the best formulation of the edible film. The edible film was made using breadfruit starch (3%, 4%, and 5% (b/v)) and beeswax (0%, 0.5%, and 1% (b/v)) as biopolymers by the casting method. Furthermore, this research was conducted to determine the quality of edible film based on its physical and chemical properties. The results showed that adding beeswax and breadfruit starch to edible films significantly affected thickness, tensile strength, elongation, solubility, transparency, moisture content, and water vapor transmission rate. The edible film with 4% breadfruit starch and 0.5% beeswax produced a better edible film than other formulations. The thickness is 0.251 mm, the tensile strength is 2.454 MPa, the elongation is 44.31%, the water vapor transmission rate (WVTR) is 6.587 g/m2/24hours, the transparency is 1.666 A/mm, the solubility is 31.77%, and the moisture content is 13.82%.